Kepentingan modal sosial dalam pertumbuhan ekonomi - Abu Bakar, Abu Sufian; Md Ali, Anizah (Universiti Utara Malaysia, 2004)
Social capital is just like one of the many forms of capital, such as physical capital, produced economic capital and human capital which has individual role that contribute to the country's growth and prosperity. Physical capital is the combination of production input and labour input in order to produce output. Human capital investment is considered as one of the catalysts to the county's growth. Nowadays, social capital is an indirect new source that contribute to the county's growth. Nevertheless, the study on contribution of social capital is still new and has various definitions. The measurement of social capital needs insight on social functioning, and the network and link between individuals in a community. All these insights can be utilised to contribute positive outcomes for the individual, ethnic group and community a like. This understanding can provide a picture of how individuals in a community cooperate in achieving mutual goals for building a prosperous county. This article looks at the role of social capital in assisting a county's economic growth. The Human Development Index (HDI) which is utilised by the World Bank will be used depict the relationship between economic growth and social capital. The regression analysis outcome on the relationship between HDI and Gross Domestic Product (GDP) shows a positive and significant relationship.